HYPOXIA AND REPRODUCTIVE HEALTH: Hypoxia and labour. Issue 1 (January 2021) - Wray, Susan; Alruwaili, Mona; Prendergast, Clodagh
Abstract : Intermittent myometrial hypoxia is a normal feature of labour, as the powerful contractions compress blood vessels. In this review, we focus on the relation between hypoxia, myometrial metabolism, and contractility. We dissect how hypoxia can feedback and limit an ongoing contraction and help prevent foetal distress. The mechanisms involve acidification from lactate, decreased excitability, and a fall of intracellular calcium concentration. As this cycle of contraction and relaxation repeats in labour, the hypoxia also engenders mechanisms that increase force; hypoxia-induced force increase, HIFI. We also discuss the role of the myometrial blood vessels in dysfunctional labour, which is associated with lactic acidosis. In synthesising these studies, we have attempted to unify findings by considering the importance of experimental protocols and finding direct mechanistic evidence from human myometrium or in vivo studies. We have made suggestions for future studies to fill the holes in our understanding and speed up the translation of our knowledge to improve births for mothers and babies everywhere.